2018
DOI: 10.1016/j.rser.2017.06.110
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renewable energy resources in Iran; with a focus on wave and tidal energy

Abstract: A growing world population and socioeconomic development are at the root of an ever-increasing energy demand throughout the world. Much of this demand is met by means of fossil fuels, leading to greenhouse gas emissions and climate change-hence the need for increasing the share of renewable energy sources in the global energy mix. Marine energy is a reliable, high-density source of energy with limited environmental impacts. Iran, with its long coastline, growing population, increasing energy demands and extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 78 publications
(104 reference statements)
0
40
0
1
Order By: Relevance
“…Consequently, it is stated that the utilization of RES frameworks is a great choice. The case study of the South Khorasan and Canary Islands presents high renewable energies shown below.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Consequently, it is stated that the utilization of RES frameworks is a great choice. The case study of the South Khorasan and Canary Islands presents high renewable energies shown below.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…The ebb and flow of the tide is used to happen at low tide. The water from the basin can be used to turn a turbine shaft thereby potential energy is converted into mechanical [7].…”
Section: Existing Wave Energyprojects a Wave Barragesmentioning
confidence: 99%
“…Geothermal energy is the energy available in the depths of the earth. It is created from solar energy that has been stored inside the earth for thousands of years [7]. Also, the collapse or decay of radioactive uranium, thorium and potassium in earth originated in a long depth mainly in areas prone to earthquakes, volcanic young and tectonic plates of earth focused.…”
Section: What Is Geothermal Energy?mentioning
confidence: 99%
“…On the other hand, fossil fuels have been used extensively in the past two decades and fossil resources are limited and one day they will end. So any country should know the energy available in it and also lookto create new ways to produce energy [7]. Also Iran has a lot of fossil resources, which could be easily used for many years, but the point to consider is, how long can these fuels be used?…”
Section: Introductionmentioning
confidence: 99%